An analysis of the impact of CD56 expression in de novo acute promyelocytic leukemia patients treated with upfront all-trans retinoic acid and anthracycline-based regimens. Issue 4 (21st March 2019) - Sobas, Marta; Montesinos, Pau; Boluda, Blanca; Bernal, Teresa; Vellenga, Edo; Nomdedeu, Josep; González-Campos, Jose; Chillón, Maria; Holowiecka, Aleksandra; Esteve, Jordi; Bergua, Juan; González-Sanmiguel, José David; et al.
Abstract: Out of 956, there were 95 (10%) CD56+ APL patients treated with PETHEMA ATRA and chemotherapy. CD56+ expression was associated with high WBC, BCR3 isoform, and co-expression of CD2, CD34, CD7, HLA-DR, CD15, and CD117 antigens. CD56+ vs CD56- APL presented higher induction death rate (16% vs 8%, p  = .02) and 5-years cumulative incidence of relapse (33% versus 10%, p  = .006), irrespectively of the Sanz score (low-risk 47% versus 5%, p  < .001; intermediate 23% versus 7%, p  < .001; and high-risk 42% versus 21%, p  = .007). In the multivariate analysis, CD56 + ( p  < .0001), higher relapse-risk score ( p  = .001), and male gender ( p  = .05) retained the independent predictive value. CD56+ APL also showed a greater risk of CNS relapse (6% versus 1%, p  < .001) and lower 5-year OS (75% versus 83%, p  = .003). The AIDA-based LPA2012 trial, with an intensified consolidation schedule for CD56+ APL, will elucidate whether an intensified consolidation schedule could mitigate the relapse rate in this setting.